Parental support in sports development of Brazilian gymnasts participants in the Olympic Games (1980-2004) - Laurita Marconi SCHIAVON; Daniela Bento SOARES (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2016)
Abstract Sports development involves important aspects that collaborate towards the achievement of a high level sports performance. Parental support is one such fact to be considered in Long Term Athlete Development (LTAD), capable of benefiting or harming athletes if not adequately administered. This study registers and discusses the importance of parental support in female Artistic Gymnastics, from the perspective of Brazilian gymnasts who have participated in the Olympic Games. The method used was Oral History with the technique known as oral testimony. The participants of the study were the ten Brazilian gymnasts who represented Brazil in the Olympic Games from when the country first participated in this championship, in 1980, up to the best Brazilian classification in Athens (2004), totaling ten gymnasts (a sample comprising 100% or the research universe). Testimony analysis was conducted through crossanalysis. The study shows unanimity among the gymnasts in regards to the importance of parental support in the sports development process. In addition to reinforcing the results found in the literature, the testimonies provide details of the relationships between the gymnasts and their families for deeper reflections around the subject, a distinguishing feature of studies with oral testimonies.